Pension Coverage for Parents and Educational Investment in Children: Evidence from Urban China. (3rd November 2015) - Mu, Ren; Du, Yang
Abstract: When social security is established to provide pensions to parents, their reliance upon children for future financial support decreases, and their need to save for retirement also falls. In this study, the expansion of pension coverage from the state sector to the non-state sector in urban China is used as a quasi-experiment to analyze the intergenerational impact of social security on education investments in children. In a difference-in-differences framework, a significant increase in the total education expenditure is found to be attributable to pension expansion. The results are unlikely to be driven by other observable trends. They are robust to the inclusion of a large set of control variables and to different specifications, including one based on the instrumental variable method.